The Influence of the Poles` Lifestyle on the Quantity and Quality of Municipal Wastewater - Płuciennik-Koropczuk, Ewelina; Myszograj, Martyna; Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents lifestyle as an important factor determining the quantity and quality of municipal wastewater. The characteristic of wastewater in Poland has changed significantly in recent years. The qualitative characteristics of municipal wastewater indicate an increase of organic compounds and in the scope of micro-contaminants identified in them, e.g. nanoparticles, microplastics, pharmaceutical and personal care products or heavy metals.
Keywords: municipal wastewater; wastewater characteristics; biodegradability; COD fractionation; PPCPs; ścieki komunalne; charakterystyka ścieków; biodegradowalność; frakcjonowanie ChZT